Style‐Related Comovement: Fundamentals or Labels? - BOYER, BRIAN H. (Journal of Finance, 2011)
ABSTRACT I find that economically meaningless index labels cause stock returns to covary in excess of fundamentals. S&P/Barra follow a simple mechanical procedure to define their Value and Growth indices. In doing so, they reclassify some stocks from Value to Growth even after their book‐to‐market ratios have risen, and vice versa. Such stocks begin to covary more with the index they join and less with the index they leave. Backdated constituent data from Barra reveal no such label‐related shifts in comovement during the 10 years prior to the actual introduction of the indices in 1992.